Languages of the nursing process in the dissertations and theses. A bibliographical study - Viviane Martins da Silva; Taciana Cavalcante de Oliveira; Marta Maria Coelho Damasceno; Thelma Leite de Araujo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The objective of this bibliographical study was to analyze trends of use of the nursing assistance systematization languages in the dissertations and theses published in the catalogs of the Center of Study and Research in Nursing, in the period from 1979 to 2004. The sample was composed of 98 abstracts that constituted research about assistance systemization or that contemplated theories with own language to a nursing process. It was observed: The concentration of studies in the Southeast and Northeast regions; The utilization of the Nanda as nursing language; The application of the Basic Human Needs Theory; The development of studies about profile and validation of diagnosis. The trends of utilization of the founded languages in this study, as well as the evidenced gaps show the need of better knowledge and comprehension to nursing process elements that give base to the classifications at its utilization in the practice, in the research and in the teaching.